47 easy-to-do classic science experiments - Provenzo, Eugene F.; Provenzo, Asterie Baker; Zorn, Peter A. (New York : Dover Publications, 1989)
Forty-seven popular science experiments of the past, all of which can be performed with household materials, and dealing with such principles as air pressure, buoyancy, gravity, inertia, and sound.
Includes bibliographical references (p. 86-88).
Adult
Keywords: Science -- Experiments -- Juvenile literature; Experiments; Science -- Experiments; Science -- Experiments